Effect of Dexamethasone in Peripheral Nerve Blocks on Recovery of Nerve Function. (January 2021) - Gagne, Oliver J.; Cheema, Amar; Abuhantash, Monther; Ree, Ron; Penner, Murray; Wing, Kevin; Younger, Alastair; Salat, Peter; Veljkovic, Andrea
Background: Peripheral nerve blocks (PNBs) have revolutionized distal extremity surgery reducing pain and improving hospital efficiency. Perineural dexamethasone has been administered with PNBs to prolong their effects, although the safety of dexamethasone has not been established in the literature. This study aimed to determine if the addition of dexamethasone affected the postoperative neurological sensory status for foot and ankle surgeries and the recovery of nerve injuries. We hypothesized that the rate of persistent nerve injury would be higher in the dexamethasone group. Methods: This is a retrospective observational cohort study of prospectively collected data of all patients from a single foot and ankle surgeon's practice. Perineural dexamethasone was routinely used as an adjunct by the regional anesthesia group until a clinical trend of increased paresthesia was found on short-term follow-up, which led to the discontinuation of its use. In this study, the cohort that received dexamethasone with ropivacaine was compared with the cohort that received ropivacaine alone. The primary outcome was a separate sensory nerve status sheet that was completed for every distal nerve territory for every patient at their follow-up visits at 2 weeks, 6 weeks, 3 months, and 6 months. Univariate analysis and a logistic regression model were used to determine the association between dexamethasone and delayed nerve recovery. A total of 250 patients were included in the study, with 117 patients in the dexamethasone group and 133 in the ropivacaine-only group. Results: The rates of nerve injuries were not different between the groups (72 [62%] in the dexamethasone group vs 79 [59%] in the ropivacaine-only group). However, nerve injury symptoms were more likely to persist and not fully recover in the dexamethasone group ( n = 47, 65%) compared with the ropivacaine-only group ( n = 32, 41%) (OR, 2.12; P = .006). Conclusion: Perineural dexamethasone added to PNBs may be associated with delayed nerve recovery after foot and ankle surgery. It may be prudent to avoid its use until its full safety profile is established in larger prospective trials. Level of Evidence: Level III, retrospective comparative study.